Geology and Geochemical Characteristics of Residual Soil From Tuff as Raw Material for Industry in Paccarammengan Area, Ujung Loe District, Bulukumba Regency, South Sulawesi Province - Fazry Parimajeng; Azikin, Busthan (Journal of Geology and Exploration, 2025)
The research area is administratively included in the Paccarammangan Area, Ujung Loe District, Bulukumba Regency, South Sulawesi Province. The purpose of this study was to conduct a study of the geochemical characteristics of rocks and residual soil from tuff in order to obtain geology regarding the characteristics of rocks and residual soil information from tuff and its use as industrial raw materials. This study was conducted using geological surface mapping methods and laboratory analysis in the form of petrographic analysis and X-Ray Fluorescence (XRF) on 4 rock samples at stations 8, 15, 16, and 48. From the results of petrographic analysis, tuff in the Walanae Formation mostly comes from intermediate-ultrabasic magma series based on its mineral composition. From the results of geochemical analysis, tuff in the Walanae Formation has a positive and negative correlation to SiO2 and the nature of its magma is intermediate-ultrabasic. Based on the naming of rocks, station 8 has a trachy basalt composition, stations 15, 16 have a basaltic andesite composition, and station 48 has a basanite composition. The use of the remaining tuff soil in the research area is suitable for use as bricks, roof tiles and fine pottery.